The aroma of the probiotic yogurts with and without supplements - Mirjana Hruškar; Ivana Bucak; Nada Vahčić (Mljekarstvo)
The purpose of this study was to establish the changes in aromacompounds of fermented milks with probiotics during storage as a function of time and temperature. The aroma compounds concentration in probiotic yogurt samples, during storage at + 4 and +20°C were studied. Acetaldehyde, diacetyl, ethanol and organic acids (lactate, acetate, citrate) content were determined during 20 days, every fifth day from the beginning of storage. Acetaldehyde, ethanol, lactic, citric and acetic acid concentration were determined using an enzymatic method, while diacetyl concentration was determined using colorimetric method. The results showed that the acetaldehyde decreased during storage. The decrease was higher at elevated temperature. On the other hand, diacetyl, ethanol and acetic acid increased during storage at both temperatures. The concentration of lactic acid increased during storage at both temperature and at the end of storage it was doubled. The amount of citric acid increased in the same manner. The increase of all organic acids during storage was higher at elevated temperature.